IEG Annual Report 2010 : Results and Performance of the World Bank Group, Main Report - Independent Evaluation Group (Washington, DC: World Bank, 2012)
Over the past year, the response to the global financial crisis has continued to dominate development and the work of international institutions, including the World Bank Group. Challenges of poverty and fragile states, environment, and climate change remain daunting. But the manner in which these are best addressed is shifting. The World Bank Group, a crucial partner in the solutions to global development, must adapt to these changes for greater development effectiveness. The International Bank for Reconstruction and Development (IBRD), the International Development Association (IDA), the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA) individually face particular challenges in the increasingly multipolar world. But there are opportunities for coordination across the World Bank Group, whether between public and business activities, among sectors, or across macro and micro concerns. Emphasizing these synergies, part one of this joint report discuss recent activities and results of the World Bank Group; part two focuses on select issues in development effectiveness at each institution. A separate volume of this report contains a detailed review and rating of management response and actions regarding recommendations from the Independent Evaluation Group (IEG) from recent years.